Green Marketing Strategies and Consumer Preferences: An Empirical Analysis of Pricing, Promotion, Packaging, and Labeling - Amarga, Mark Francis R.; Esmero, Jereco D.; Seriño, Niña Lee; Alonzo, Albert A.; Degoma, Junaisah Nissi L.; Aguhob, Renz P. (International Review of Management and Marketing, 2026)
Growing consumer awareness of environmental issues has reshaped purchasing behavior, creating demand for sustainable and eco-friendly products. Businesses are increasingly adopting green marketing strategies to respond to this shift, yet limited research has been conducted in localized contexts such as the Philippines. Understanding how key marketing mix elements influence consumer preferences for green products is vital for both theory and practice. This study aimed to examine the influence of green marketing strategies in terms of price, promotion, packaging, and labeling on consumer buying preferences for green products in Naawan, Misamis Oriental. Specifically, it sought to determine which factors most significantly predict consumer choices and how these elements interact in shaping sustainable consumption. A quantitative, descriptive-correlational research design was employed. Data were collected from 300 respondents using a structured questionnaire and analyzed through correlation and regression techniques to measure the strength and predictive power of each marketing variable. Results revealed that all four variables significantly influence consumer preference, with promotion exerting the strongest effect, followed by price, packaging, and labeling. These findings indicate that effective promotional strategies and competitive pricing are the most powerful drivers of green product adoption, while sustainable packaging and credible labeling play important but comparatively supportive roles. The study contributes to the growing body of green marketing literature by highlighting localized consumer behavior. It underscores the importance for businesses and policymakers to integrate promotional, pricing, and sustainability practices to strengthen market acceptance and environmental responsibility.